Qube - Quantum key distribution with CubeSat - Lemke, Norbert M.K.; Weinfurter, Harald; Marquardt, Christoph; Moll, Florian; Haber, Roland; Grünefeld, Matthias; Seidel, Stephan T.; Freiwang, Peter; Rosenfeld, Wenjamin; Bayraktar, Ömer; Rödiger, Benjamin; Schmidt, Christopher; et al. (Proceedings of the International Astronautical Congress, IAC, 2018)
QUBE (Quantum Key Distribution with CubeSat) is one out of three pilot projects in the frame of the national German initiative QUTEGA to promote quantum technologies. The project is funded by the German Federal Ministry of Education and Research (BMBF) with co-funding of industry as preparation for the European flagship on Quantum Technology. With the current development pace in quantum computation, it has been predicted that in less than two decades quantum computers will be able to break encryption codes deployed today, which are currently based on mathematical problems difficult to solve with classical computation. This shows the urgent need for quantum-safe encryption that is resistant to attacks of both, quantum and classical, computers. A long term solution for quantum-safe encryption is the use of a completely random, so-called One-Time-Pad generated with true Random Number Generation (RNG) and distributed via Quantum Key Distribution (QKD). The QKD in fiber networks is limited to approx. 100 km due to damping within the carrier medium. For longer distances so far only satellite based techniques are able to transmit the keys. As a pathfinder, QUBE plans perform an in-orbit demonstration of the core technologies on a CubeSat platform.
CRIS-Team Scopus Importer:2022-06-05
Keywords: CubeSat; QKD; QRNG; Quantum Mechanics; QUBE